Small farmer s integration strategy in the exporting chain (2019)
Export-oriented agriculture in Peru has significant development, which generates encouraging ex-pectations for economy. In this context, small farmers must be integrated, which is why the article aims to expose what is happening with small farmers and necessary actions for its integration into the exporting chain. Bibliography related to Peruvian agriculture was selected, considering what is happening in other Latin American countries that are also going through similar processes imple-mentation of new products and entry to new foreign markets . To obtain primary source information, experts were interviewed and a survey to small farmers in the district of Lunahuaná was applied, results of both are included in the respective annexes; expectations that small farmers have in this process are also presented.